Alterations in Oral–Nasal–Pharyngeal Microbiota and Salivary Proteins in Mouth-Breathing Children - Fan, Cancan; Guo, Lihong; Gu, Haijing; Huo, Yongbiao; Lin, Huancai (Frontiers in Microbiology, 2020)
Mouth breathing induces a series of diseases, while the influence on microbiota of relative cavity and salivary proteins remains unknown. In this study, for the first time, profiles of oral-nasal-pharyngeal microbiota among mouth breathing children (MB group, n=10) were compared with paired nose breathing children (NB group, n=10) using 16S rDNA (V3-V4 region) high-throughput sequencing. The differentially expressed salivary proteins were revealed using label-free quantification (LFQ) method, and their associations with bacterial abundance were measured by canonical correspondence analysis (CCA). The overall bacterial profiles differ between the two groups and the differences were related to the duration of mouth breathing. The diversity of oral-pharyngeal microbiota increased significantly, and the nasal-pharyngeal species tended to be consistent (unweighted UniFrac, p=0.38) in MB group. Opportunistic pathogens were localized as follows: Acinetobacter in the anterior supragingival plaque; Neisseria in unstimulated saliva; Streptococcus pneumoniae in the pharynx and Stenotrophomonas in the nostrils. Oxidative stress-related salivary proteins (lactoylglutathione lyase and peroxiredoxin-5) were up-regulated, while immune-related proteins (integrin alpha-M and proteasome subunit alpha type-1) were down-regulated. The differentially expressed proteins were associated with specific bacteria, indicating their potentials as candidate biomarkers for the diagnosis, putatively early intervention and therapeutic target of mouth breathing. This study showed that mouth breathing influences the oral-nasal-pharyngeal microbiota and enriches certain pathogens, accompanied with the alterations in the salivary environment. Further research on the pathologic mechanisms and dynamic changes in longitudinal studies are warranted.